2019
DOI: 10.1002/adma.201904905
|View full text |Cite
|
Sign up to set email alerts
|

Mild Innate Immune Activation Overrides Efficient Nanoparticle‐Mediated RNA Delivery

Abstract: Clinical mRNA delivery remains challenging, in large part because how physiology alters delivery in vivo remains underexplored. For example, mRNA delivered by lipid nanoparticles (LNPs) is being considered to treat inflammation, but whether inflammation changes delivery remains understudied. Relationships between immunity, endocytosis, and mRNA translation led us to hypothesize that TLR4 activation reduced LNP-mediated mRNA delivery. We therefore quantified LNP uptake, endosomal escape, and mRNA translation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 63 publications
1
73
0
1
Order By: Relevance
“…As mRNA molecules are vulnerable to ribonuclease enzymes that widely exist in the biological systems and highly negatively charged, which compromise their internalization through cell membranes, suitable in vivo mRNA delivery systems are urgently needed (4). To protect and deliver mRNA, extensive efforts have been devoted to construct biocompatible carriers, such as LNPs, polymeric nanoparticles, peptides/protein-mRNA complexes, and other types of biomaterials (9,22,23). Among these reported platforms, lipid-like nanoparticles (LLNs) are one of the representative materials that have been extensively used for mRNAs delivery in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…As mRNA molecules are vulnerable to ribonuclease enzymes that widely exist in the biological systems and highly negatively charged, which compromise their internalization through cell membranes, suitable in vivo mRNA delivery systems are urgently needed (4). To protect and deliver mRNA, extensive efforts have been devoted to construct biocompatible carriers, such as LNPs, polymeric nanoparticles, peptides/protein-mRNA complexes, and other types of biomaterials (9,22,23). Among these reported platforms, lipid-like nanoparticles (LLNs) are one of the representative materials that have been extensively used for mRNAs delivery in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…To test this hypothesis, we synthesized a series of novel adamantyl‐phospholipids and quantified how 109 LNPs functionally delivered mRNA (i.e., mRNA translated into protein) to 16 cell‐types in mice (i.e., in vivo). This systematic high throughput in vivo assay 18‐20 forgoes traditional cell culture experiments. Our data suggest performing drug delivery studies directly in vivo is important; specifically, we found that in vitro nanoparticle delivery can be a poor predictor of in vivo nanoparticle delivery 21 .…”
Section: Resultsmentioning
confidence: 99%
“…To isolate the effect of constrained phospholipids on LNP formation, we used a lipid‐PEG(C 14 PEG 2000 ), cholesterol (cholesterol, 20α‐hydroxycholesterol, β‐sitosterol), and ionizable lipid (cKK‐E15) components that were previously characterized (Figure 2a), and utilized four different molar ratios (Figure 2b). In order to perform a high throughput in vivo study, we utilized Fast Identification of Nanoparticle Delivery 20 (FIND), a workflow 18‐20 that quantifies mRNA delivery mediated by many LNPs in a single mouse. Briefly, we used microfluidics to formulate 120 LNPs with Cre mRNA and a unique DNA barcode; LNP‐1, with chemical structure 1, carried Cre mRNA and DNA barcode 1, whereas LNP‐N, with chemical structure N, carried Cre mRNA and DNA barcode N. We performed a quality control analysis on all 120 LNPs by quantifying the size of each LNP using dynamic light scattering.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, mRNA delivery was rescued by inhibiting PKR and TLR4 with small molecules, illustrating the value of understanding cellular pathways that block the translation of therapeutic mRNA. 90 Modified mRNAs have been used in mRNA drugs treating CF patients. Specifically, Translate Bio, an mRNA company, is currently evaluating a treatment for CF known as MRT5005.…”
Section: Chemically Modifying Mrna Drugs Improves Their Safety and Efmentioning
confidence: 99%